Le paysage comme outil de planification territoriale du risque incendie : le cas des interfaces habitat-forêt (IHF) en région méditerranéenne - Jeanne Ravoire; Jordan Szcrupak; Marion Brun; Yves Petit-Berghem (Projets de Paysage)
Against the backdrop of global warming, the spread of fire risks is undermining France’s firefighting strategy, particularly in wildland-urban interfaces (WUI) in the Mediterranean region. Faced with this problem, a scientific consensus is emerging around the need for a paradigm shift in the prevention of fire risks with an emphasis on reducing vulnerability. Through an investigation into stakeholder interactions involved in the WUI between Marseille and the Parc national des Calanques and an analysis of the regulatory tools used in the Massif des Maures in the face of new fire hazards, this article looks at how the landscape can be positioned as a concerted planning tool for WUIs exposed to fire risk. The results show that sociocultural obstacles arise from a social distancing from risk and a compartmentalisation of inhabitants and institutional risk managers. In addition, they show that regulatory tools are unable to address the challenges of reducing collective vulnerability. Considering the landscape as a tool that can integrate fire risks in regional planning addresses the problem of the collective representation of risk and communication between the different stakeholders. Given an experimental status, WUIs thus appear to be conducive to innovative projects offering the potential for shared governance in the proactive management of fire hazards.